2019
DOI: 10.3390/su11247179
|View full text |Cite
|
Sign up to set email alerts
|

Building Inter-Personal Competence in Architecture and Urban Design Students through Smart Cities at a Higher Education Institution

Abstract: As the smart city concept and applications continue to evolve, traditional architects and urban designers are facing an increasingly uncertain future. This paper outlines an innovative educational format to bolster and perpetuate the interdisciplinary nature of architects and urban designers that resonates with both sustainable development (SD) and smart cities (SCs). By applying ‘connective knowledge’ to the concept of interdisciplinarity education, a method was established that uses the SC concept to expand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
3
3
0
Order By: Relevance
“…These findings confirm a significant positive impact of the green-smart campus initiative on both student engagement and the university's corporate image, thus providing support for the proposed hypotheses (H1, H2, and H3). These findings are in line with previous research emphasizing the importance of sustainability initiatives in higher education and their potential to enhance students' experiences and perceptions of the institution (Babar et al, 2020;Ha, 2019).…”
Section: Research Results Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings confirm a significant positive impact of the green-smart campus initiative on both student engagement and the university's corporate image, thus providing support for the proposed hypotheses (H1, H2, and H3). These findings are in line with previous research emphasizing the importance of sustainability initiatives in higher education and their potential to enhance students' experiences and perceptions of the institution (Babar et al, 2020;Ha, 2019).…”
Section: Research Results Discussionsupporting
confidence: 92%
“…The observed positive impact of the green-smart campus initiative on the university's corporate image (b = .317, p = .000) underscores the significance of sustainability efforts in shaping the institution's reputation. Students and other stakeholders tend to perceive an institution that prioritizes environmental responsibility as more socially responsible and forward-thinking (Ha, 2019). This positive corporate image not only attracts prospective students but also elevates the university's standing within the broader community and among potential partners and donors (Babar et al, 2020).…”
Section: Research Results Discussionmentioning
confidence: 99%
“…First, the findings reveal how the students of the SSC study programs should be able to transcend disciplinary boundaries, perceive SSC problems, and develop expertise on possible solutions and their consequences. These findings fall in line with [25], [35], [37] that support a "blended" approach toward the development of master courses, drawing from the richness and diversity of available content. Our study also revealed that the analyzed programs promote diverse learning environments that cover different dimensions of sustainability, exceed boundaries and involve learners in applying digital tools and methods of data analysis to smart urban development.…”
Section: Discussionsupporting
confidence: 89%
“…According to UNESCO [37, p. 9], education for sustainable development: converges the Sustainable Development agendas; addresses the environmental, societal and economic dimensions of sustainability; increases stakeholder and local engagement; promotes the whole-institution approach; engages formal, nonformal and informal education; is interdisciplinary; uses a variety of pedagogical and activating methods. This observation is in line with [30], [35], [36], [38].…”
Section: Education For Sscssupporting
confidence: 88%
See 1 more Smart Citation